HERITAGE TOURISM INDEX: SURVEY AND DOCUMENTATION OF NATIONAL HERITAGE INVENTORY FOR THE TOURISM INDUSTRY IN THE STATE OF NORTH MALAYSIA PENINSULA - Bin Paidi, Zulhilmi; Binti AB Ghani, Rohani (Universitas Islam Negeri Alauddin Makassar, 2015)
Heritage Tourism Index (Heritage Tourism Index): Survey and Documentation of National Heritage Inventory (Historic Buildings and Heritage Site) for the Tourism Industry in the States Of North Malaysia Peninsula. This study was conducted to survey and document all national heritage treasure (historic buildings and heritage), which belongs to the national heritage inventory of Malaysia, particulary those who were found in the northern states like in Peninsula, Perak, Penang, Kedah and Perlis. The findings, which will be put into a list, are to be used as a tour index by industrial tourism of Malaysia to generate more income. Using Malaysia's national heritage inventory, this study will be performed objectively to trace all informations related to the historic buildings and sites in the northern state of Malaysia, and to survey and document the national heritage thoroughly. After that, the results of the survey and documentation will be classified and categorized to produce a complete index of Malaysian heritage information to use as an essential guide for heritage tourist industry. It will become important tool and guideline for this country's tourism industry.